Building a network of ADPKD reference centres across Europe: the EuroCYST initiative - Petzold, Katja; Gansevoort, Ron T; Ong, Albert C M; Devuyst, Olivier; Rotar, Laura; Eckardt, Kai-Uwe; Köttgen, Anna; Pirson, Yves; Remuzzi, Giuseppe; Sandford, Richard; Tesar, Vladimir; Ecder, Tevfik; et al. (Nephrology, dialysis, transplantation, 2014)
BACKGROUND: Autosomal dominant polycystic kidney disease (ADPKD) is the most common monogenic inherited kidney disease, affecting an estimated 600 000 individuals in Europe. The disease is characterized by age-dependent development of a multiple cysts in the kidneys, ultimately leading to end-stage renal failure and the need of renal replacement therapy in the majority of patients, typically by the fifth or sixth decade of life. The variable disease course, even within the same family, remains largely unexplained. Similarly, assessing disease severity and prognosis in an individual with ADPKD remains difficult. Epidemiological studies are limited due to the fragmentation of ADPKD research in Europe. METHODS: The EuroCYST initiative aims: (i) to harmonize and develop common standards for ADPKD research by starting a collaborative effort to build a network of ADPKD reference centres across Europe and (ii) to establish a multicentric observational cohort of ADPKD patients. This cohort will be used to study factors influencing the rate of disease progression, disease modifiers, disease stage-specific morbidity and mortality, health economic issues and to identify predictive disease progression markers. Overall, 1100 patients will be enrolled in 14 study sites across Europe. Patients will be prospectively followed for at least 3 years. Eligible patients will not have participated in a pharmaceutical clinical trial 1 year before enrollment, have clinically proven ADPKD, an estimated glomerular filtration rate (eGFR) of 30 mL/min/1.73 m(2) and above, and be able to provide written informed consent. The baseline visit will include a physical examination and collection of blood, urine and DNA for biomarker and genetic studies. In addition, all participants will be asked to complete questionnaires detailing self-reported health status, quality of life, socioeconomic status, health-care use and reproductive planning. All subjects will undergo annual follow-up. A magnetic resonance imaging (MRI) scan will be carried out at baseline, and patients are encouraged to undergo a second MRI at 3-year follow-up for qualitative and quantitative kidney and liver assessments. CONCLUSIONS: The ADPKD reference centre network across Europe and the observational cohort study will enable European ADPKD researchers to gain insights into the natural history, heterogeneity and associated complications of the disease as well as how it affects the lives of patients across Europe.
Keywords: Polycystic Kidney, Autosomal Dominant; magnetická rezonanční tomografie; hodnoty glomerulární filtrace; Prognosis; konziliární vyšetření a konzultace; EuroCYST; ADPKD; longitudinální studie; mladý dospělý; Longitudinal Studies; Humans; Standard of Care; standardní péče; výzkumný projekt; Biomarkers; risk factors; Young Adult; prognóza; biologické markery; lidé; průzkumy a dotazníky; cohort; Research Design; Surveys and Questionnaires; Europe; Glomerular Filtration Rate; Magnetic Resonance Imaging; Referral and Consultation; zdravotnické služby; Health Services; Evropa; Health Status; biomarker; polycystické ledviny autozomálně dominantní; zdravotní stav